Reduce hot spot stresses in welded connections of orthotropic steel bridge decks by using UHPC layer: Experimental and numerical investigation. (1st October 2020) - Abdelbaset, Hesham; Cheng, Bin; Tian, Liang; Li, Hai-Ting; Zhang, Qing-Hua
Highlights: Rib-to-deck-to-floor beam connections in UHPC reinforced orthotropic steel decks were tested. Structural hot spot stresses at critical locations of RDF welded connections were investigated. Effects of employing UHPC overlay on reducing hot spot stresses were analyzed. Effects of key parameters on hot spot stresses were numerically evaluated. Abstract: Orthotropic steel decks (OSDs) are widely used in long span steel bridges owing to their outstanding structural characteristics and lightweight; however, the fatigue resistance of OSDs is still a prominent problem of such deck structures. Ultra-High-Performance Concrete (UHPC) has been recently employed in orthotropic steel decks to enhance their structural behavior and extend their fatigue life. In this paper, experimental work has been carried out to investigate the effect of employing UHPC overlay on the hot spot stresses at fatigue prone details of OSDs. Three full scale rib-to-deck-to-floor beam (RDF) welded connections were fabricated and tested. One centric wheel load was applied; so that, the effect of in-plane and out-of-plane distortions of floor beam web can be considered. In parallel with the experimental program, a finite element (FE) analysis was also performed. Upon validation of FE models against experimental results, a parametric study was carried out to study the effect of key structural parameters that primarily influence the hot spot stresses. Experimental results indicated that, the stresses around floor beam cut-out were slightly higher than the hot spot stresses at considered locations on U-rib due to in-plane and out-of-plane distortions of the floor beam web under centric loading. The application of 60 mm UHPC layer effectively reduced the hot spot stresses by 26–83% at the considered locations of the test specimens. Results of parametric study indicated that, increasing UHPC layer thickness significantly enhanced the stiffness of the bridge deck and therefore effectively reduced the hot spot stresses at considered spots. On the other hand, the effect of increasing UHPC elastic modulus slightly influenced the hot spot stresses at considered locations and its effect is deemed neglectable.